Algebra 2 (1st Edition)

Published by McDougal Littell
ISBN 10: 0618595414
ISBN 13: 978-0-61859-541-9

Chapter 6 Rational Exponents and Radical Functions - 6.4 Use Inverse Functions - 6.4 Exercises - Skill Practice - Page 443: 17


See below

Work Step by Step

We need to show that $f(g(x))=x=g(f(x))$ $f(g(x))=f((4x)^{1/3})=\frac{1}{4}((4x)^{1/3})=\frac{1}{4}(4x)^{\frac{1}{3}\times3}=\frac{1}{4}4x=x$ $g(f(x))=g(\frac{1}{4}x^3)=(4(\frac{1}{4}x^3))^{1/3}=(x^3)^{1/3}=x^{3\times\frac{1}{3}}=x^1=x$ Thus we proved what we had to.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.